Local Food-Based Supplementary Feeding Education and Mothers’ Nutrition Knowledge for Underweight Children - Sally Peni Andriana Huliselan Huliselan; Sevana Christina Mayaut (Innovative Approaches in Health Science Journal, 2026)
Background: Maternal knowledge is an important component of appropriate feeding practices for children with undernutrition. In geographically remote settings, nutrition education that uses familiar and accessible local foods may improve the relevance of supplementary feeding messages. Objective: To evaluate the effect of local food-based supplementary feeding education on mothers’ knowledge regarding nutrition for underweight children in the working area of Leksula Public Health Center, Maluku, Indonesia. Methods: A quasi-experimental pretest-posttest study with a control group was conducted in October 2025. Thirty mothers of underweight children were selected purposively from a population of 42 and allocated to intervention (n=15) and control (n=15) groups. The intervention consisted of one approximately 60-minute educational session using a leaflet and a structured educational plan focused on local food-based supplementary feeding. Knowledge was measured using a 20-item multiple-choice questionnaire (score 0-20). Because the data were non-normally distributed, within-group changes were analyzed using the Wilcoxon signed-rank test and between-group differences using the Mann-Whitney U test. Results: In the control group, the proportion of mothers with high knowledge increased slightly from 66.7% at pretest to 73.3% at posttest, with no significant within-group change (p=0.317). In the intervention group, high knowledge increased from 40.0% at pretest to 80.0% at posttest, while moderate knowledge decreased from 60.0% to 20.0%; the within-group change was significant (p=0.030). Baseline knowledge did not differ significantly between groups (p=0.070), whereas posttest knowledge was significantly higher in the intervention group (p